2019
DOI: 10.3390/f10111000
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Comparative Analysis of the Complete Chloroplast Genome of a Mangrove Plant: Scyphiphora hydrophyllacea Gaertn. f. and Related Rubiaceae Species

Abstract: Scyphiphora hydrophyllacea Gaertn. f. (Rubiaceae) is an endangered mangrove species found in China, and its only known location is in Hainan Island. Previous studies conducted on S. hydrophyllaceae have mainly focused on its location, biological characteristics, and medical effects. However, to date, there has been no published report regarding the genetics or genome of this endangered mangrove species. In this study, we developed valuable chloroplast genome-related molecular resources of S. hydrophyllaceae by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
11
17
0
Order By: Relevance
“…In total, 41 perfect SSRs were detected in C. sprucearum cp genome distributed in the LSC, SSC, and IR regions with strong A/T bias. Similarly, previous studies also revealed that the noncoding region contained more SSRs than the coding regions [14,16]. Also our results are comparable to those of several previous studies showing that SSRs in cp genomes are highly rich in polythymine (poly T) or polyadenine (polyA) as reported for cp genomes of other plants species [32][33][34].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In total, 41 perfect SSRs were detected in C. sprucearum cp genome distributed in the LSC, SSC, and IR regions with strong A/T bias. Similarly, previous studies also revealed that the noncoding region contained more SSRs than the coding regions [14,16]. Also our results are comparable to those of several previous studies showing that SSRs in cp genomes are highly rich in polythymine (poly T) or polyadenine (polyA) as reported for cp genomes of other plants species [32][33][34].…”
Section: Discussionsupporting
confidence: 91%
“…The GC content in the IR region was much higher than in the LSC and SSC region in C. spruceanum cp genome, probably due to the presence of eight ribosomal RNA (rRNA) genes in this region, which is consistent with previous analyses in other Ixoroideae [15,16], and in other angiosperms cp genomes [14,22,23]. The IR (A/B) region has always been considered consistent and stable in the cp genome, and it is also common in the evolution of plants with contraction or expansion events in the border region [16]. Also, these results suggest that the cp genome in this subfamily had rather conserved genome organization [15,16].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations